Application of Jigsaw Learning Method Using Play Money Learning Media to Improve Mathematics Learning Outcomes - Fitriani, Rina Eka (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to improve mathematics learning outcomes about money in class III semester I SDN 4 Mangin, Karangrayung District, Grobogan Regency, 2017/2018 academic year through toy money media and the application of Jigsaw learning method. The research subjects were grade 3 students at SDN 4 Mangin, totaling 14 students. The research design is classroom action research consisting of two cycles. Each cycle consists of 2 meetings. Data collection techniques using evaluation in the form of assignments, worksheets and evaluation questions. While the data analysis includes qualitative data and quantitative data. Learning outcomes from the pre-cycle were obtained, from 14 students, only 5 students (36%) had reached the mastery target with a minimum score of 65. In the first cycle, classical completeness was 71%. While in the second cycle of 100%. These results indicate that the application of the Jigsaw method using toy money media can improve mathematics learning outcomes for grade 3 students at SDN 4 Mangin.